- 32
- 0
On my process of obtaining the IF for solving a differential equation, I got stuck with an equation as following. This could be a very simple algebra problem, but I just can't do it. Would someone tell me if I can factor the numerators by (x^4 + 1) for the first equation and by (x^4 -1) for the second equation so that I can have only x or y as a variable?
[(x^4 - 1) - (5*x^4 + 1)]/x*(x^4+1) = (-4*x^4 - 2)/x(x^4 + 1)
= -2(2*x^4 +1)/x(x^4 + 1)
[(5*x^4 + 1) - (x^4 - 1)]/y*(x^4-1) = (4x^4 + 2)/y(x^4 - 1)
=2(2*x^4 + 1)/y(x^4 - 1)
Thanks for your help in advance.
[(x^4 - 1) - (5*x^4 + 1)]/x*(x^4+1) = (-4*x^4 - 2)/x(x^4 + 1)
= -2(2*x^4 +1)/x(x^4 + 1)
[(5*x^4 + 1) - (x^4 - 1)]/y*(x^4-1) = (4x^4 + 2)/y(x^4 - 1)
=2(2*x^4 + 1)/y(x^4 - 1)
Thanks for your help in advance.